Pengaruh Kemampuan Menghafal Al Qur’an Dan Motivasi Berprestasi Terhadap Prestasi Belajar Peserta Didik Program Tahfidz - Hafiah Hafidhotul Ilmiyah; Ainul Halim; Mustadi Mustadi (Pascasarjana Universitas Qomaruddin, 2025)
This study aims to analyze the effect of the ability to memorize the Qur'an and achievement motivation on the learning achievement of students in the tahfidz program at MAN 1 Gresik. The ability to memorize the Qur'an not only trains memory and concentration, but also develops discipline and time management skills, which contribute to improving learning achievement. Achievement motivation, which reflects the internal drive to achieve high goals, also plays an important role in determining how much effort students put into learning and facing academic challenges. The research method used is a quantitative method with a research population of 60 students from the tahfidz program at MAN 1 Gresik, with a random sampling technique (sample random sampling). The data collection technique used a questionnaire containing 40 structured statements and using a Likert scale as a measuring tool for use. The data were then analyzed by regression testing using SPSS 15.0 for windows. The results of the analysis showed that the ability to memorize the Qur'an and achievement motivation together had a positive and significant effect on student learning achievement with a multiple regression sig test with a sig value of 0.000 <0.05 and an R Square value of 80.7%. Students who have high memorization ability and strong achievement motivation tend to have better learning achievement than students with lower ability and motivation. This finding emphasizes the importance of integrating the tahfidz program with strategies to increase achievement motivation in an effort to improve the quality of education. The tahfidz program supported by a motivational approach can be an effective solution in optimizing students' academic potential at MAN 1 Gresik.